Effectiveness and Safety of Abrocitinib in Patients with Moderate-to-Severe Atopic Dermatitis: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Hammad Ali Fadlalmola; Muayad Saud Albadrani; Amal Mohamed Elhusein; Wahieba E. Mohamedsalih; Veerabhadra D. S. Swamy; Daniel Mon Mamanao (Hindawi Limited, 2021)
Background. Atopic dermatitis (AD) is a complex, chronic, inflammatory skin disease characterized by pruritic, intense itching, and eczematous lesions affecting about 25% of children and 2% to 3% of adults worldwide. Abrocitinib is a selective inhibitor of Janus kinase-1 (JAK1) enzyme inhibiting the inflammatory process. Therefore, we aimed to assess the efficacy and safety of abrocitinib for moderate-to-severe AD. Methods. We systematically searched PubMed, Cochrane, Web of Science, Scopus, and EczemATrials till Feb 1, 2021, for reliable trials. The analysis was conducted using an inverse-variance method. The results were pooled as mean difference/event rate and 95% confidence interval. Results. Abrocitinib 100 mg and 200 mg were associated with higher IGA response, EASI-50% responders, EASI-75% responders, EASI-90% responders, number of participants with at least 4-point improvements in NRS, and quality of life measured by DLQI and CDLQI than placebo. Also, 100 mg and 200 mg were associated with lower SCORAD index, %BSA, PSAAD index, and POEM index than placebo. Abrocitinib 100 mg and 200 mg were not associated with adverse events such as upper respiratory tract infection, nasopharyngitis, dermatitis, atopic, any serious adverse events, and death. Conclusion. Abrocitinib in dose 100 mg or 200 mg is an effective, well-tolerated, and promising drug in treating patients with moderate-to-severe atopic dermatitis. However, the analysis favored the efficacy of abrocitinib 200 mg over 100 mg, but side effects such as nausea and headache are likely to occur more with 200 mg.